New cultural studies : adventures in theory - Hall, Gary, 1962-; Birchall, Clare (Edinburgh University Press, 2006)
What should or could cultural studies look like in the 21st Century? New Cultural Studies is both an introductory reference work and an original study which explores some of the most exciting new directions currently being opened up in cultural studies. A new generation has begun to emerge from the shadow of the Birmingham School: a generation who have turned to theory as a means to think through some of the crucial problems and issues in contemporary culture. New Cultural Studies: Adventures in Theory collects for the first time the ideas of this generation and explains just why theory continues to be crucial for cultural studies.